Duloxetine-induced Sleep Bruxism in Fibromyalgia Successfully Treated With Amitriptyline - Şule Şahin Onat (Acta Reumatológica Portuguesa, 2015)
A 44-year-old woman, who was suffering from widespread musculoskeletal pain, fatigue, and sleep disorder, was diagnosed as fibromyalgia. There was no apparent organic disease. Duloxetine therapy was introduced with a dose of 60 mg/day at bedtime. A few days later her husband noted severe teeth clenching and associated loud grinding noises during sleep. Then, duloxetine dosage was reduced to 30 mg/day. The bruxism continued with this dosage, thus the therapy was discontinued. The bruxism resolved after cessation. Three weeks later, duloxetine therapy was restarted at the dosage of 60 mg/day. On the third day of the therapy, bruxism started again and amitriptyline therapy at the dosage of 10 mg/day was added to duloxetine therapy. The dosage of amitriptyline was incrementally adjusted to 25 mg/ day. On the fourth day of the combined therapy, bruxism symptoms improved. Two months later, the bruxism symptoms were resolved and the complaints for fibromyalgia were under control. Although bruxism has been reported due to venlafaxine use, there is only one duloxetine-induced bruxism case in the literature which was treated with buspirone. However, we report duloxetine-induced bruxism treated successfully with amitriptyline in a patient with fibromyalgia. Tricyclic antidepressants have a suppression effect on the REM phase of the sleep cycle; this may help to cease the bruxism symptoms appearing in that phase of the sleep cycle. This is the first reported case of fibromyalgia with duloxetine-induced sleep bruxism successfully treated with amitriptyline.